An analysis of institutional dynamic for industrial symbiosis in the United Kingdom - Geglia, Domenico (2015)
Industrial symbiosis is an industrial concept that points to the exchange of resources between companies. Among several cases around the world as Kalundborg, TEDA and Styria none of these had a program on a national level encouraged by the government. In the United Kingdom the concept was funding from 2005 to 2014. The National Industrial Symbiosis Programme (NISP) born in 2000 by International Synergies Ltd and has excellent results in economic, environmental and social space. The British institutional context has become highly competitive and ever more dependent on others in a continue changing, so this work aims to understand if institutional dynamics in the UK support or impede the development of industrial symbiosis? Based on this research question the study followed the general objective of understanding the development of industrial symbiosis in the UK overtime influenced by institutional context. The study was conducted as a case study of industrial symbiosis in the UK using a series of open-end interviews with the actors involved. Through a content analysis were individuated key categories and concepts related to them which resulted in the construction of a conceptual framework for UK industrial symbiosis. The UK institutional context encouraged the creation of NISP which produces with satisfactory results the development of industrial symbiosis participating in the development of institutional capacities between organizations involved, although they were not completely fomented. Industrial symbiosis in the UK is struggling to move forward because the government is not financing the NISP and a short-term view of the companies made this batch process and probably for a review of development mechanisms. This study has appointed to a strengthening of cooperation between government and company accompanied by cultural change of the waste management as source of opportunity for companies, so an educational process that promotes this is fundamental to the future of industrial symbiosis in the UK. Finally, this study has appointed to the continuation of funding by government and the dissemination and sharing of results and practices at the national level for the institutionalization of industrial symbiosis.